NAC Candidate Gene Marker for bgm-1 and Interaction With QTL for Resistance to Bean Golden Yellow Mosaic Virus in Common Bean - Soler-Garzón, Alvaro; Oladzad, Atena; Beaver, James; Beebe, Stephen; Lee, Rian; Lobaton, Juan David; Macea, Eliana; McClean, Phillip; Raatz, Bodo; Rosas, Juan Carlos; Song, Qijian; Miklas, Phillip N. (Frontiers in Plant Science, 2021)
Genetic resistance is the primary means for control of Bean golden yellow mosaic virus (BGYMV) in common bean (Phaseolus vulgaris L.). Breeding for resistance is difficult because of sporadic and uneven infection across field nurseries. We sought to facilitate breeding for BGYMV resistance by improving MAS for the recessive bgm-1 gene and to identify and develop MAS for quantitative trait loci (QTL) conditioning resistance. Genetic linkage mapping in two recombinant inbred line populations, and GWAS in a large breeding population and two diversity panels revealed a candidate gene for bgm-1 and three QTL BGY4.1, BGY7.1 and BGY8.1 on independent chromosomes. A mutation (5 bp deletion) in a NAC (No Apical Meristem) domain transcriptional regulator superfamily protein gene Phvul.003G027100 on chromosome Pv03 corresponded with the recessive bgm-1 resistance allele. The 5 bp deletion in exon 2 starting at 20 bp (Pv03: 2,601,582) is expected to cause a stop codon at codon 23 (Pv03: 2,601,625) disrupting further translation of the gene. A Tm-shift assay marker named PvNAC1 was developed to track bgm-1. PvNAC1 corresponded with bgm-1 across ~1000 lines which traces bgm-1 back to a single landrace ‘Garrapato’ from Mexico. BGY8.1 has no effect on its own but exhibited a major effect when combined with bgm-1. BGY4.1 and BGY7.1 acted additively, and they enhanced the level of resistance when combined with bgm-1. Tm-shift assay markers were generated for MAS of the QTL but their effectiveness requires further validation.